Cold Water Immersion Enhanced Athletes’ Wellness and 10-m Short Sprint Performance 24-h After a Simulated Mixed Martial Arts Combat - Tabben, Montassar; Ihsan, Mohammed; Ghoul, Nihel; Coquart, Jeremy; Chaouachi, Anis; Chaabene, Helmi; Tourny, Claire; Chamari, Karim (Frontiers in Physiology, 2018)
Objective: The aim of the present study was to examine the effect of Cold Water Immersion (CWI) on the recovery of physical performance, hematological stress markers and perceived wellness (i.e., Hooper scores) following a simulated Mixed Martial Arts (MMA) competition. Method: Participants completed two experimental sessions in a counter-balanced order (CWI or passive recovery for control condition: CON), after a simulated MMAs competition (3×5-min MMA rounds separated by 1-min of passive rest). During CWI, athletes were required to submerge their bodies, except the trunk, neck and head, in the seated position in a temperature-controlled bath (~ 10°C) for 15-min. During CON, athletes were required to be in a seated position for 15-min in same room ambient temperature. Venous blood samples (creatine kinase, cortisol, and testosterone concentrations) were collected at rest (PRE-EX, i.e., before MMAs), immediately following MMAs (POST-EX), immediately following recovery (POST-R) and 24 h post MMAS (POST-24), whilst physical fitness (squat jump, countermovement-jump and 5- and 10-m sprints) and perceptual measures (well-being Hooper index: fatigue, stress, delayed onset muscle soreness (DOMS), and sleep) were collected at PRE-EX, POST-R and POST-24, and at PRE-EX and POST-24, respectively. Results: The main results indicate that POST-R sprint (5- and 10-m) performances were ‘likely to very likely’ (d = 0.64 and 0.65) impaired by prior CWI. However, moderate improvements were in 10-m sprint performance were ‘likely’ evident at POST-24 after CWI compared with CON (d = 0.53). Additionally, the use of CWI ‘almost certainly’ resulted in a large overall improvement in Hooper scores (d = 1.93). Specifically, CWI ‘almost certainly’ resulted in improved sleep quality (d = 1.36), stress (d = 1.56) and perceived fatigue (d = 1.51), and ‘likely’ resulted in a moderate decrease in DOMS (d = 0.60). Conclusion: The use of CWI resulted in an enhanced recovery of 10-m sprint performance, as well as improved perceived wellness 24-h following simulated MMA competition.